The Application of The Word "Lembaga" Method In Improving The Articulation Ability of Hearing Impairment in Second Grade of Elementary Special School Sumbersari - Endang Rusyani; Fika Annisa Sabrina; Risti Ragadhita (Indonesian Journal of Community and Special Needs Education, 2022)
The purpose of this study was to determine the effect of the application of the word method for the "LEMBAGA" word on improving the articulation ability to hear impairment students in the second grade of elementary special school. This study uses the Single Subject Research (SSR) method with an A-B-A design on one elementary special school student with a hearing impairment student. The learning method begins with the introduction of a particular word. This word is then broken down into syllables, syllables into letters. Next, letters are the process of arranging letters into syllables and syllables into words. The results showed that there was an increase in the child's articulation ability before and after the intervention was given. The application of the word "Lembaga" method is used by showing children how to write a word and a picture of the word, thus children are more interested in participating in learning.